Long-term outcomes of ablation, liver resection, and liver transplant as first-line treatment for solitary HCC of 3 cm or less using an intention-to-treat analysis: A retrospective cohort study. (May 2022) - Ivanics, T.; Rajendran, L.; Abreu, P.A.; Claasen, M.P.A.W.; Shwaartz, C.; Patel, M.S.; Choi, W.J.; Doyle, A.; Muaddi, H.; McGilvray, I.D.; Selzner, M.; Beecroft, R.; et al.
Abstract: Background: Curative-intent therapies for hepatocellular carcinoma (HCC) include radiofrequency ablation (RFA), liver resection (LR), and liver transplantation (LT). Controversy exists in treatment selection for early-stage tumours. We sought to evaluate the oncologic outcomes of patients who received either RFA, LR, or LT as first-line treatment for solitary HCC ≤ 3 cm in an intention-to-treat analysis. Materials and methods: All patients with solitary HCC ≤ 3 cm who underwent RFA, LR, or were listed for LT between Feb-2000 and Nov-2018 were analyzed. Cox regression analysis was then performed to compare intention-to-treat (ITT) survival by initial treatment allocation and disease-free survival (DFS) by treatment received in patients eligible for all three treatments. Results: A total of 119 patients were identified (RFA n = 83; LR n = 25; LT n = 11). The overall intention-to-treat survival was similar between the three groups. The overall DFS was highest for the LT group. This was significantly higher than RFA (p = 0.02), but not statistically significantly different from LR (p = 0.14). After multivariable adjustment, ITT survival was similar in the LR and LT groups relative to RFA (LR HR:1.13, 95%CI 0.33–3.82; p = 0.80; LT HR:1.39, 95%CI 0.35–5.44; p = 0.60). On multivariable DFS analysis, only LT was better relative to RFA (LR HR:0.52, 95%CI 0.26–1.02; p = 0.06; LT HR:0.15, 95%CI 0.03–0.67; p = 0.01). Compared to LR, LT was associated with a numerically lower hazard on multivariable DFS analysis, though this did not reach statistical significance (HR 0.30, 95%CI 0.06–1.43; p = 0.13) Conclusion: For treatment-naïve patients with solitary HCC ≤ 3 cm who are eligible for RFA, LR, and LT, adjusted ITT survival is equivalent amongst the treatment modalities, however, DFS is better with LR and LT, compared with RFA. Differences in recurrence between treatment modalities and equipoise in ITT survival provides support for a future prospective trial in this setting. Highlights: Ablation, resection, and transplantation can cure hepatocellular carcinoma (HCC). For patients with solitary HCC≤3 cm controversy exists in treatment selection. Ablation, resection, and transplantation have similar intention-to-treat survival. The disease-free survival is better with liver resection and liver transplantation.